FAMILY COMMUNICATION WITH CHILDREN IN PREVENTING THE NEGATIVE IMPACTS OF GADGETS AT PESONA BATANG KUIS RESIDENCE HOUSING COMPLEX - Trisusanti Kaloko; Irwansyah Irwansyah; Hasan Sazali (Journal Analytica Islamica, 2026)
This research is motivated by the need to communicate in the family with the negative impact of using gadgets on children. Therefore, this study aims to determine the extent of parental understanding of the appropriate use of gadgets in children, also to find out the obstacles experienced by parents, and to find out the efforts made by people to prevent the negative impact of using gadgets on children.This type of research is a qualitative research with a case study method, The research subjects are families, especially parents and also the object of the research is family communication to children to prevent the negative impact of using gadgets on children. The data collection methods used observation, in-depth interviews and documentation.. The results showed that family knowledge, especially parents, about family communication with children in preventing the negative impact of gadgets on children.